2014
DOI: 10.1007/s11590-014-0772-4
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of simplicial partitioning for Lipschitz optimization problems with linear constraints

Abstract: The well known DIRECT (DIviding RECTangles) algorithm for global optimization requires bound constraints on variables and does not naturally address additional linear or nonlinear constraints. A feasible region defined by linear constraints may be covered by simplices, therefore simplicial partitioning may tackle linear constraints in a very subtle way. In this paper we demonstrate this advantage of simplicial partitioning by applying a recently proposed deterministic simplicial partitions based DISIMPL algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 39 publications
(46 reference statements)
0
20
0
Order By: Relevance
“…However, simplex partitions were applied in a similar algorithm called DISIMPL [32][33][34]42]. Experiments showed, that the proposed simplicial DISIMPL algorithm gives very competitive results to the DIRECT algorithm using standard test problems and performs particularly well when the search space and the numbers of local and global minimizers may be reduced by taking into account symmetries of the objective function.…”
Section: Modifications and Applications Of The Direct Algorithmmentioning
confidence: 99%
“…However, simplex partitions were applied in a similar algorithm called DISIMPL [32][33][34]42]. Experiments showed, that the proposed simplicial DISIMPL algorithm gives very competitive results to the DIRECT algorithm using standard test problems and performs particularly well when the search space and the numbers of local and global minimizers may be reduced by taking into account symmetries of the objective function.…”
Section: Modifications and Applications Of The Direct Algorithmmentioning
confidence: 99%
“…Although BO has been used to solve global optimization problems in bounded-box search spaces [1-3, 7, 8, 18], more interesting and realistic cases are related to constrained global optimization (CGO) [19][20][21], where constraints are not defined as simple limits on the values of the variables spanning the search space. The traditional way of solving the constrained problems consists in solving an unconstrained problem where the original objective function is penalized depending on the violation of feasibility.…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, there is little work of the DIRECT-type algorithm for constrained problems (Jones 2001;Finkel 2005;Paulavičius and Žilinskas 2016). Finkel (2005) compared three constrainthandling techniques and revealed that the penalty method is better for DIRECT.…”
Section: Introductionmentioning
confidence: 99%
“…Finkel (2005) compared three constrainthandling techniques and revealed that the penalty method is better for DIRECT. Paulavičius and Žilinskas (2016) presented a simplicial partitioning-based DIRECT algorithm to handle linear constraints.…”
Section: Introductionmentioning
confidence: 99%